Recommendations for the Development of Cell-Based Anti-Viral Vector Neutralizing Antibody Assays - Gorovits, Boris; Fiscella, Michele; Havert, Mike; Koren, Eugen; Long, Brian; Milton, Mark; Purushothama, Shobha (The AAPS journal, 2020)
Viral vector–based gene therapies (GTx) have received significant attention in the recent years and the number of ongoing GTx clinical trials is increasing. A platform of choice for many of these studies is adeno-associated virus (AAV). All humans may be exposed to natural AAV infections and could mount an immune response against the virus. Consequently, there can be a high prevalence of pre-existing anti-AAV immunity. This presents a potential limitation for AAV-based GTx due to the potential for AAV-specific antibodies to reduce the efficacy of the GTx. Therefore, appropriate assessment of potential subjects enrolled in these studies should include evaluation for the presence and degree of anti-AAV immunity, including anti-AAV neutralizing antibodies (NAb). Recommendations for the development and validation of cell-based anti-AAV NAb detection methods, including considerations related to selection of appropriate cell line, surrogate vector/reporter gene, assay matrix and controls, and methodologies for calculating assay cut-point are discussed herein. General recommendations for the key assay validation parameters are provided as well as considerations for the development of NAb diagnostic tests. This manuscript is produced by a group of scientists involved in GTx therapeutic development representing various companies. It is our intent to provide recommendations and guidance to industrial and academic laboratories working on viral vector based GTx modalities with the goal of achieving a more consistent approach to anti-AAV NAb assessment.